Critical Storytelling in Uncritical Times Stories Disclosed in a Cultural Foundations of Education Course - Hartlep, Nicholas D.; Hensley, Brandon O.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2015)
"Critical Storytelling in Uncritical Times shares the stories of students and a professor in a Cultural Foundations of Education Course. Storytellers in this volume grapple with issues of white privilege, racial microaggressions, bullying , cultural barriers, immigration, and other forms of struggle in educational settings. The disciplinary backgrounds of the authors are diverse: Psychology, Communication Studies, Higher Education Administration, and Educational Foundations. The authors write stories about their role(s) in resisting (or failing to resist) hegemony, and their contributions draw attention to critical problems scholars and practitioners find in 21st century schooling. This anthology was planned, written, and edited by course participants. The stories shared in each chapter were completely at the discretion of the author. By making themselves vulnerable, participants investigated stories that mattered to them. This book engages a community of critical voices in an uncritical age.".
Keywords: Education; Education; Education, general; Electronic books